047. Comparison of Single-Port and Three-Port Laparoscopic Appendicitis Techniques in Adult Appendicitis - Wibisono, Prathama; Jeo, Wifanto Saditya (JBN (Jurnal Bedah Nasional), 2024)
Background : Laparoscopic appendectomy (LA) become the standard for treatment of appendicitis in many countries, offering benefits such as quick recovery, fewer postoperative complications, and good cosmetic outcomes. Minimally invasive surgical techniques like single-port laparoscopic appendectomy (SPLA) are increasingly performed for better cosmetic results. However, the outcomes and safety of this technique compared to conventional three-port laparoscopic appendectomy (CTLA) still debated among experts. To compare the outcomes between SPLA and CTLA in adult appendicitis, focusing on outcomes such as postoperative wound infection rates, operating time, and surgical costs. Methods : Comprehensive search through various online databases such as PubMed, ScienceDirect, Scopus, Cochrane, and Google Scholar from 2014-2024 was performed. This research was conducted following the PRISMA guidelines. Oxford Evidence-Based Medicine criteria to assess the quality of the paper. Articles that fulfilled the eligibility criteria were retrieved and extracted for study characteristics and outcomes. Results: Four studies met the inclusion criteria, 434 patients undergoing either SPLA or CTLA procedures. There were no significant differences in complication rates such as wound infection and ileus between the two techniques. Conclusion: The SPLA technique is safe and reliable option with advantages in better cosmetic outcomes and shorter hospital stay duration, despite requiring longer operating time compared to CTLA.